Pengaruh Penggunaan Obat Nyamuk Coil Dan Mat Elektrik Terhadap Sel Darah Mencit (Mus Musculus, L.) - Prastiwi, Esya Putri; , Dra. Hariyatmi, M.Si (2015)
THE INFLUENCE OF MOSQUITO COIL AND VAPORIZING MAT AGAINST MICE (Mus musculus, L.) BLOOD CELLS Esya Putri Prastiwi, A420110124, Study Program of Biology, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta, 2015, forty-six pages. ABSTRACT Insect repellent is one type of insect killer pesticide (insecticide). Mosquito repellent coil (mosquito coil) with brand Baygon contains the active ingredient d-allethrin and transflutrin were respectively 0.1% and 0.028%, while the mosquito repellent electric mat (vaporizing mat) with brand Baygon contains the active ingredient d-allethrin as 40mg/ (21g) or 0.19% and transflutrin as 3mg/21g or by 0,014%. This study aims to determine the effect of exposure to mosquito repellent coil and the electric mat to the blood cells of mice (Mus musculus, L). The method used was completely randomized design (CRD) with 1 factor that is repellent to the treatment A0 (Without exposure repellent), A1 (coil, 4 hours / day), A2 (coil, 8 hours / day), A3 (coil, 12 hours / day), A4 (mat, 4 hours / day), A5 (mat, 8 hours / day) A6 (mat, 12 hours / day) for 20 days, each with three replications. On the last day of the surgery to take blood from the heart, were counted against the number of red blood cells and white blood cells using a haemocytometer, while to determine levels of hemoglobin using Haemometer. The results showed that exposure to mosquito repellent coil and electric mat effect on blood cells in mice which includes the number of red blood cells, white blood cell count and hemoglobin level, as indicated by sig 0.003 <0.05. Based on the results of LSD test indicated that treatment with the electric mat immersion treatment time 4, 8, and 12 hours more influence on blood cells. This is evidenced by p-value of <0.05, so it can be concluded treatment with the electric mat treatment time 4, 8, and 12 hours affects the blood cells. . Word key: mosquito coil, vaporizing mat, red blood cells, white blood cells, hemoglobin.